A light / heat responsive shape memory polyimide-based phase change composite material and preparation method thereof
By preparing polyimide-based phase transformation composite materials, the problem of poor deformation performance of polyimide-based aerogels is solved by using methods such as condensation polymerization, solvent exchange, freeze-drying and vacuum impregnation, and the light/thermal response shape memory performance is achieved to meet the needs of shape memory performance materials.
Patent Information
- Application Number
- CN202310234552.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-03-13
AI Technical Summary
The deformation performance of polyimide-based aerogels cannot meet the needs of shape memory performance materials.
Polyamic acid gel was obtained by condensation and polymerization, solvent exchange and freeze-drying, forming a water-soluble precursor PAA, and then dispersed and composited with hydroxylated carbon nanotubes (CNTOH) and cobalt acetate in aqueous solution. After heat treatment and vacuum impregnation of polyethylene glycol, a light/thermal response shape memory polyimide-based phase change composite material was prepared.
The optical/thermal response shape memory performance of polyimide-based phase-change composite materials is achieved, with good porosity and mechanical properties, and can heat up under light to achieve shape recovery, meeting the needs of shape memory performance materials.
Smart Images

Figure CN116444855B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a light / heat responsive shape memory polyimide-based phase change composite material and a preparation method thereof, belonging to the technical field of polymer-based nanocomposite materials. Background Art
[0002] Shape memory material (SMM) is a smart material with shape memory effect. After deformation, it can return to its original shape under appropriate stimulation. SMM consists of two parts, one is called fixed phase, which provides permanent deformation, and the other is called reversible phase, which provides temporary deformation ability. With the deepening of research, people found that phase change material can also be used as a switch of SMM to fix temporary shape, and the switching temperature is usually the phase change temperature.
[0003] Phase change materials (PCMs) are widely recognized as a potential latent heat storage material, which has attracted extensive attention in energy-saving buildings, electronic equipment thermal management, biomedical systems, etc. However, most organic PCMs have problems such as easy leakage during phase change, poor light adsorption, and strong rigidity, making it difficult to achieve good contact in closed thermal energy management devices. In order to overcome the problems of liquid leakage and weak light absorption, impregnation of PCMs into three-dimensional porous materials has become the focus of extensive research.
[0004] Polyimide aerogel has the advantages of high porosity, high specific surface area, and high temperature resistance due to its highly permeable three-dimensional micro-network structure. It is widely used in aerospace, thermal insulation materials, sound insulation materials, flame retardant materials, flexible materials, shock absorbing materials, and energy storage devices. However, the current polyimide aerogel materials have disadvantages such as large volume shrinkage and poor thermal conductivity, resulting in poor deformation performance and unable to meet the demand for shape memory performance materials. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that the deformation performance of polyimide-based aerogel is poor and cannot meet the requirements of shape memory performance materials.
[0006] The present invention provides a light / heat responsive shape memory polyimide-based phase change composite material and a preparation method thereof. The preparation of the light / heat responsive shape memory polyimide-based phase change composite material comprises: using diamine and dianhydride monomers for condensation polymerization to obtain a polyimide precursor polyamic acid gel, performing solvent exchange to obtain a water-soluble precursor PAA, and then reacting PAA, hydroxylated carbon nanotubes (CNTs) OH ) and cobalt acetate were dispersed in aqueous solution and PI / CNT was prepared by freeze drying and high temperature heat treatment. OH / Co composite aerogel, and then the phase change material polyethylene glycol is loaded on PI / CNT by vacuum impregnation OH / Co composite aerogel, and drying the water to obtain a polyimide-based phase change composite material with good light / thermal response and shape memory properties.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] The first object of the present invention is to provide a method for preparing a light / thermal responsive shape memory polyimide-based phase change composite material, the method comprising the following steps:
[0009] (1) a diamine monomer and a dianhydride monomer are subjected to a condensation polymerization reaction in an organic solvent to obtain a polyimide precursor polyamic acid gel, the obtained polyamic acid gel is placed in water for solvent exchange, and after completion, freeze-dried to obtain water-soluble polyamic acid filaments (PAA);
[0010] (2) adding the PAA prepared in step (1) to the hydroxylated carbon nanotube aqueous dispersion to dissolve it, and adding triethylamine to assist dissolution, and after the PAA is completely dissolved, adding cobalt acetate, and continuously stirring and dispersing to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion;
[0011] (3) injecting the mixed dispersion obtained in step (2) into a mold, placing the mold in a freezer for freeze molding, and then freeze drying after molding to obtain PAA / CNT OH / Co composite aerogel, and then PAA / CNT OH / Co composite aerogel is heat treated to obtain PI / CNT OH / Co composite aerogel;
[0012] (4) In a vacuum environment, the PI / CNT obtained in step (3) OH The / Co composite aerogel is immersed in a polyethylene glycol aqueous solution, and the water is dried after the immersion to obtain a light / thermal responsive shape memory polyimide-based phase change composite material.
[0013] In one embodiment of the present invention, the diamine monomer in step (1) includes one or more of 4,4'-diaminodiphenyl ether (ODA), 2,2'-bis(trifluoromethyl)-(1,1'-diphenyl)-4,4'-diamine (TFMB), and p-phenylenediamine (PDA); the dianhydride monomer includes one or more of biphenyltetracarboxylic dianhydride (BPDA), hexafluorodianhydride (6-FDA), bisphenol A type diether dianhydride (BPADA), 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride (BTDA), and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA); the molar ratio of the diamine monomer to the dianhydride monomer is 1:(0.8-1.5); preferably 1:(1.05-1.2).
[0014] In one embodiment of the present invention, the organic solvent in step (1) comprises any one of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide.
[0015] In one embodiment of the present invention, the mass ratio of triethylamine to PAA in step (2) is 1:2-3; the mass ratio of hydroxylated carbon nanotubes to PAA is 1:(2.5-6); and the mass ratio of hydroxylated carbon nanotubes to cobalt acetate is 8:(1-6).
[0016] In one embodiment of the present invention, the PAA in step (2) is dissolved in the hydroxylated carbon nanotube aqueous dispersion for 12-24 hours, and the stirring and dispersion time after adding cobalt acetate is continued for 2-12 hours.
[0017] In one embodiment of the present invention, the freezing molding temperature in the freezer in step (3) is -120 to -20°C, and the freezing molding time is 2 to 8 hours.
[0018] In one embodiment of the present invention, the freeze-drying temperature in step (3) is -90 to -60°C, and the freeze-drying time is 48 to 96 hours.
[0019] In one embodiment of the present invention, the heat treatment in step (3) is carried out in a tubular furnace under an argon atmosphere, and the heat treatment process is: 0.5 to 1.5 h at 100 to 150 ° C, 0.5 to 1.5 h at 200 to 250 ° C, and 0.5 to 2.5 h at 300 to 350 ° C.
[0020] In one embodiment of the present invention, the concentration of the polyethylene glycol (PEG) aqueous solution in step (4) is 50 to 500 mg / ml, preferably 500 mg / ml, and the immersion time is 1 to 4 hours.
[0021] In one embodiment of the present invention, the drying in step (4) is carried out in a vacuum oven for 12 to 48 hours.
[0022] The second object of the present invention is to provide a light / thermal responsive shape memory polyimide-based phase change composite material prepared by the above method.
[0023] The third object of the present invention is to provide an application of the above-mentioned light / heat responsive shape memory polyimide-based phase change composite material in the preparation of heat storage materials, light-heat conversion and smart devices.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention prepares a light / thermal responsive shape memory polyimide aerogel composite material for the first time by freeze drying and vacuum impregnation, and the preparation process is simple and low in cost.
[0026] (2) The polyimide / hydroxylated carbon nanotube / cobalt three-dimensional aerogel skeleton in the light / thermal responsive shape memory polyimide aerogel composite material of the present invention has a very high porosity, which provides a spatial basis for the loading of polyethylene glycol; the composite material is temporarily fixed in shape and deformed back by the phase change of polyethylene glycol, and the relatively low phase transition temperature of polyethylene glycol enables the composite material to heat up under light to above the phase transition temperature, thereby achieving light-responsive shape memory performance; wherein, polyimide is used as a matrix to construct a three-dimensional aerogel network structure, and polyimide has excellent thermal stability (decomposition temperature above 450°C), corrosion resistance and radiation resistance, and has excellent shape stability, thermal stability and chemical stability; hydroxylated carbon nanotubes are used as a physical crosslinker to be composited with polyimide, and the abundant hydroxyl groups on the surface of the hydroxylated carbon nanotubes interact with the polyimide through hydrogen bonds, which enhances its mechanical properties to a certain extent. At the same time, due to the rigidity of the carbon nanotubes, the volume shrinkage of the composite aerogel can be effectively reduced. In addition, hydroxylated carbon nanotubes, as typical carbon materials, have good heat absorption and heat transfer properties, which can improve the photothermal conversion capacity and heat transfer rate of the composite aerogel, improve the thermal absorption efficiency of polyethylene glycol, and thus improve the shape memory performance.
[0027] By introducing cobalt ions into the polyimide composite, the cobalt ions can not only coordinate with polyamic acid, but also coordinate with hydroxylated carbon nanotubes, thereby forming a double cross-linked network inside the polyimide composite aerogel, further improving the mechanical properties of the composite aerogel; using polyethylene glycol as the phase change material, it has the characteristics of high phase change latent heat, adjustable phase change temperature, and being green and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a microstructure diagram of the polyimide / hydroxylated carbon nanotube / cobalt composite aerogel before loading PEG in Example 2 of the present invention;
[0029] Figure 2 This is a microstructure diagram of the shape memory polyimide-based phase change composite material finally prepared in Example 2 of the present invention;
[0030] Figure 3 This is a graph showing the thermal response of the shape recovery process during the shape memory performance test of the shape memory polyimide-based phase change composite material prepared in Example 2 of the present invention;
[0031] Figure 4This is a diagram showing the optical response of the shape recovery process during the shape memory performance test of the shape memory polyimide-based phase change composite material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0033] The present invention relates to a method for measuring the mechanical properties and memory properties of a light / thermal responsive shape memory polyimide-based phase change composite material:
[0034] 1. Determination of mechanical properties
[0035] The compressive mechanical properties of PI and PI composite aerogels without PEG loading were analyzed using a universal testing machine (UTM); the shape of the tested aerogel was a cube, and each sample was compressed 5 times. Its stress-strain curve was tested with the strain set to 50%, and the compression modulus and compression strength were calculated based on the curve.
[0036] 2. Determination of shape recovery rate
[0037] Shape recovery rate (R r ) was tested by a dynamic thermomechanical analyzer, and the determination formula is as follows:
[0038]
[0039] Where ε represents the fixed strain value after the external force is removed, ε re It represents the strain recovery value after heating, and N represents the number of steps in a shape memory cycle.
[0040] Example 1
[0041] A method for preparing a light / heat responsive shape memory polyimide-based phase change composite material, the method comprising the following steps:
[0042] (1) Weigh 10 mmol of 4,4'-diaminodiphenyl ether (ODA) and 10.5 mmol of biphenyltetracarboxylic anhydride (BPDA); add 10 mmol of ODA to 35 ml of N-methylpyrrolidone (NMP) in an ice bath and stir to dissolve, then add 10.5 mmol of BPDA in 5 equal portions after dissolution, react for 3 hours, add 3.1 ml of triethylamine, and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours and then used;
[0043] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly flowing the polyamic acid gel obtained in the above step (1) into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;
[0044] (3) dissolving 1 g of the polyamic acid filaments obtained in step (2) above in 40 ml of an 8 mg / ml aqueous dispersion of hydroxylated carbon nanotubes, adding 0.5 g of triethylamine to accelerate the dissolution, and stirring and dispersing for 12 hours to obtain a polyamic acid / hydroxylated carbon nanotube aqueous dispersion; adding 0.16 g of cobalt acetate to the polyamic acid / hydroxylated carbon nanotube aqueous dispersion, and continuing to stir for 6 hours to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion;
[0045] (4) pouring the polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion obtained in the above step (3) into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt composite aerogel;
[0046] (5) placing the polyamic acid / hydroxylated carbon nanotube / cobalt ion composite aerogel obtained in the above step (4) into a tubular furnace, and imidizing the polyamic acid at high temperature under an argon atmosphere, wherein the high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 2 hours, to finally obtain a polyimide / hydroxylated carbon nanotube / cobalt composite aerogel;
[0047] (6) The polyimide / hydroxylated carbon nanotube / cobalt ion composite aerogel obtained in the above step (5) is immersed in a 50 mg / ml aqueous solution of polyethylene glycol under a vacuum environment for 1 hour, and then the water-containing composite material is placed in a 100° C. vacuum oven for drying for 12 hours to remove moisture, thereby obtaining a light and heat dual-responsive shape memory phase change composite material with the polyimide / hydroxylated carbon nanotube / cobalt composite aerogel as the skeleton.
[0048] Example 2
[0049] A method for preparing a light / heat responsive shape memory polyimide-based phase change composite material, the method comprising the following steps:
[0050] (1) Weigh 10 mmol ODA and 10.5 mmol BPDA; first add 10 mmol ODA to 35 ml NMP in an ice bath and stir to dissolve, then add 10.5 mmol BPDA in 5 equal portions after dissolution, react for 3 hours, add 3.1 ml triethylamine, and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours before use;
[0051] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly flowing the polyamic acid gel obtained in the above step (1) into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;
[0052] (3) dissolving 1 g of the polyamic acid filaments obtained in step (2) above in 40 ml of an 8 mg / ml aqueous dispersion of hydroxylated carbon nanotubes, adding 0.5 g of triethylamine to accelerate the dissolution, and stirring and dispersing for 12 hours to obtain a polyamic acid / hydroxylated carbon nanotube aqueous dispersion; adding 0.16 g of cobalt acetate to the polyamic acid / hydroxylated carbon nanotube aqueous dispersion, and continuing to stir for 6 hours to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion;
[0053] (4) pouring the polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion obtained in the above step (3) into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt composite aerogel;
[0054] (5) placing the polyamic acid / hydroxylated carbon nanotube / cobalt ion composite aerogel obtained in the above step (4) into a tubular furnace, and imidizing the polyamic acid at high temperature under an argon atmosphere, wherein the high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 2 hours, to finally obtain a polyimide / hydroxylated carbon nanotube / cobalt composite aerogel;
[0055] (6) The polyimide / hydroxylated carbon nanotube / cobalt ion composite aerogel obtained in the above step (5) is immersed in a 100 mg / ml aqueous solution of polyethylene glycol under a vacuum environment for 2 hours, and then the water-containing composite material is placed in a 100° C. vacuum oven for drying for 24 hours to remove moisture, thereby obtaining a light and heat dual-responsive shape memory phase change composite material with the polyimide / hydroxylated carbon nanotube / cobalt composite aerogel as the skeleton.
[0056] Example 3
[0057] A method for preparing a light / heat responsive shape memory polyimide-based phase change composite material, the method comprising the following steps:
[0058] (1) Weigh 10 mmol ODA and 10.5 mmol BPDA; first add 10 mmol ODA to 35 ml NMP in an ice bath and stir to dissolve, then add 10.5 mmol BPDA in 5 equal portions after dissolution, react for 3 hours, add 3.1 ml triethylamine, and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours before use;
[0059] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly flowing the polyamic acid gel obtained in the above step (1) into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;
[0060] (3) dissolving 1 g of the polyamic acid filaments obtained in step (2) in 40 ml of an 8 mg / ml aqueous dispersion of hydroxylated carbon nanotubes, and adding 0.5 g of triethylamine to accelerate the dissolution. After stirring and dispersing for 12 hours, a polyamic acid / hydroxylated carbon nanotube aqueous dispersion was obtained. 0.16 g of cobalt acetate was added to the polyamic acid / hydroxylated carbon nanotube aqueous dispersion, and stirring was continued for 6 hours to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion.
[0061] (4) pouring the polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion obtained in the above step (3) into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt composite aerogel;
[0062] (5) placing the polyamic acid / hydroxylated carbon nanotube / cobalt ion composite aerogel obtained in the above step (4) into a tubular furnace, and performing imidization of the polyamic acid and reduction of graphene oxide at high temperature in an argon atmosphere, wherein the high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 2 hours, to finally obtain a polyimide / hydroxylated carbon nanotube / cobalt composite aerogel.
[0063] (6) The polyimide / hydroxylated carbon nanotube / cobalt ion composite aerogel obtained in the above step (5) is immersed in a 200 mg / ml polyethylene glycol aqueous solution under a vacuum environment for 3 hours, and then the water-containing composite material is placed in a 100° C. vacuum oven for drying for 36 hours to remove moisture, thereby obtaining a light and heat dual-responsive shape memory phase change composite material with the polyimide / hydroxylated carbon nanotube / cobalt composite aerogel as the skeleton.
[0064] Example 4
[0065] A method for preparing a light / heat responsive shape memory polyimide-based phase change composite material, the method comprising the following steps:
[0066] (1) Weigh 10 mmol ODA and 10.5 mmol BPDA; first add 10 mmol ODA to 35 ml NMP in an ice bath and stir to dissolve, then add 10.5 mmol BPDA in 5 equal portions after dissolution, react for 3 hours, add 3.1 ml triethylamine, and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours before use;
[0067] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly flowing the polyamic acid gel obtained in the above step (1) into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;
[0068] (3) dissolving 1 g of the polyamic acid filaments obtained in step (2) in 40 ml of an 8 mg / ml aqueous dispersion of hydroxylated carbon nanotubes, and adding 0.5 g of triethylamine to accelerate the dissolution. After stirring and dispersing for 12 hours, a polyamic acid / hydroxylated carbon nanotube aqueous dispersion was obtained. 0.16 g of cobalt acetate was added to the polyamic acid / hydroxylated carbon nanotube aqueous dispersion, and stirring was continued for 6 hours to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion.
[0069] (4) pouring the polyamic acid / hydroxylated carbon nanotube / cobalt ion mixed dispersion obtained in the above step (3) into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt composite aerogel;
[0070] (5) placing the polyamic acid / hydroxylated carbon nanotube / cobalt ion composite aerogel obtained in the above step (4) into a tubular furnace, and performing imidization of the polyamic acid and reduction of graphene oxide at high temperature in an argon atmosphere, wherein the high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 2 hours, to finally obtain a polyimide / hydroxylated carbon nanotube / cobalt composite aerogel.
[0071] (6) The polyimide / hydroxylated carbon nanotube / cobalt ion composite aerogel obtained in the above step (5) is immersed in a 500 mg / ml aqueous solution of polyethylene glycol under a vacuum environment for 4 hours, and then the water-containing composite material is placed in a 100° C. vacuum oven for drying for 48 hours to remove moisture, thereby obtaining a light and heat dual-responsive shape memory phase change composite material with the polyimide / hydroxylated carbon nanotube / cobalt composite aerogel as the skeleton.
[0072] Embodiment 5-9
[0073] The only difference from Example 4 is that the amount of cobalt acetate in step (3) is adjusted to 0.04 g, 0.08 g, 0.24 g, 0.32 g and 0.64 g respectively, and the other parameters and conditions are the same as those in Example 4.
[0074] Comparative Example 1
[0075] The only difference from Example 4 is that the adjustment step (3) is as follows: 1 g of polyamic acid filaments is dissolved in 40 ml of ultrapure water, and 0.5 g of triethylamine is added to accelerate the dissolution, and the polyamic acid aqueous dispersion is obtained after stirring and dispersing for 12 hours; the other parameters and steps are the same as those in Example 4.
[0076] Comparative Example 2
[0077] The only difference from Example 4 is that the adjustment step (3) is as follows: 1 g of polyamic acid filaments is dissolved in 40 ml of 8 mg / ml aqueous dispersion of hydroxylated carbon nanotubes, and 0.5 g of triethylamine is added to accelerate the dissolution. After stirring and dispersing for 12 hours, a polyamic acid / hydroxylated carbon nanotube aqueous dispersion is obtained; the other parameters and steps are the same as those in Example 4.
[0078] Comparative Example 3
[0079] The only difference from Example 4 is that the adjustment step (3) is as follows: 1 g of polyamic acid filaments is dissolved in 40 ml of 4 mg / ml cobalt acetate aqueous dispersion, and 0.5 g of triethylamine is added to accelerate the dissolution, and after stirring and dispersing for 12 hours, a polyamic acid / cobalt ion mixed dispersion is obtained; the other parameters and steps are the same as those in Example 4.
[0080] Comparative Example 4
[0081] The only difference from Example 4 is that the operation of step (6) is omitted, and other parameters and conditions are the same as those of Example 4.
[0082] Performance measurement
[0083] 1. Structural characterization of photo- / thermal-responsive shape memory polyimide-based phase change composites
[0084] Figure 1 The polyimide / hydroxylated carbon nanotube / cobalt composite aerogel (PI / CNT OH / Co) microscopic pore structure, the pore size is below 100μm, the pore size distribution is relatively uniform, and the pores are arranged in an orderly manner. The uniform and orderly pore structure is the basis for good mechanical properties.
[0085] Figure 2 The polyimide / hydroxylated carbon nanotube / cobalt composite aerogel (PI / CNT OH / Co) after loading PEG, because PEG is loaded on the aerogel pore wall, compared with PI / CNT OH The Si / Co composite aerogels have thicker pore walls and are able to fix temporary shapes.
[0086] Figure 3 This is a demonstration of the thermal response process of the shape memory process of the sample in Example 2 after the shape is compressed and fixed and then heated on a hot stage. The hot stage temperature is 100°C and the recovery time is 240s.
[0087] Figure 4 This is a demonstration of the light response process of the shape memory process of the sample in Example 2 after being compressed and fixed and then irradiated under infrared light, with a recovery time of 330s.
[0088] 2. The shape recovery rate and light response performance of the light / heat responsive shape memory polyimide-based phase change composite materials prepared in Examples 1 to 9 and Comparative Examples 1 to 4 were measured. The results are shown in Tables 1 and 2:
[0089] Table 1. Mechanical properties and memory properties of phase change composite materials prepared in Examples 1 to 9
[0090]
[0091]
[0092] Table 2. Mechanical and memory properties of the phase change composite materials of Example 4 and Comparative Examples 1 to 4
[0093]
Claims
1. A method for preparing a light / thermal responsive shape memory polyimide-based phase change composite material, characterized in that: The method comprises the following steps: (1) a diamine monomer and a dianhydride monomer are subjected to a condensation polymerization reaction in an organic solvent to obtain a precursor polyamic acid gel, and the obtained polyamic acid gel is placed in water for solvent exchange. After the reaction is completed, the polyamic acid gel is freeze-dried to obtain polyamic acid filaments; (2) adding the polyamic acid filaments obtained in step (1) into a hydroxylated carbon nanotube aqueous dispersion to dissolve the polyamic acid filaments, and adding triethylamine, and adding cobalt acetate after the polyamic acid filaments are completely dissolved, and continuously stirring and dispersing to obtain a mixed dispersion of polyamic acid / hydroxylated carbon nanotubes / cobalt ions; the mass ratio of triethylamine to polyamic acid filaments is 1:(2-3); the mass ratio of hydroxylated carbon nanotubes to polyamic acid filaments is 1:(2.5-6); and the mass ratio of hydroxylated carbon nanotubes to cobalt acetate is 8:(1-6); (3) injecting the mixed dispersion obtained in step (2) into a mold, and placing the mold in a freezer for freeze molding, and then freeze drying after molding to obtain a polyamic acid / hydroxylated carbon nanotube / cobalt composite aerogel, and then heat treating the polyamic acid / hydroxylated carbon nanotube / cobalt composite aerogel to obtain a polyimide / hydroxylated carbon nanotube / cobalt composite aerogel; (4) In a vacuum environment, the polyimide / hydroxylated carbon nanotube / cobalt composite aerogel obtained in step (3) is immersed in a polyethylene glycol aqueous solution, and the moisture is dried after the immersion to obtain a light / thermal responsive shape memory polyimide-based phase change composite material.
2. The method according to claim 1, characterized in that The diamine monomer in step (1) includes one or more of 4,4'-diaminodiphenyl ether (ODA), 2,2'-bis(trifluoromethyl)-(1,1'-diphenyl)-4,4'-diamine (TFMB) and p-phenylenediamine (PDA); the dianhydride monomer includes one or more of biphenyltetracarboxylic dianhydride (BPDA), hexafluorodianhydride (6FDA), bisphenol A type diether dianhydride (BPADA), 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride (BTDA) and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA); the molar ratio of the diamine monomer to the dianhydride monomer is 1:(0.8-1.5).
3. The method according to claim 1, characterized in that The organic solvent in step (1) includes any one of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide.
4. The method according to claim 1, characterized in that: The freezing molding temperature in the freezer in step (3) is -120 to -20°C, and the freezing molding time is 2 to 8 hours.
5. The method according to claim 1, characterized in that The freeze-drying temperature in step (3) is -90 to -60°C, and the freeze-drying time is 48 to 96 hours.
6. The method according to claim 1, characterized in that The heat treatment in step (3) is carried out in a tubular furnace under an inert atmosphere, and the heat treatment process is: 0.5 to 1.5 h at 100 to 150° C., 0.5 to 1.5 h at 200 to 250° C., and 0.5 to 2.5 h at 300 to 350° C.
7. The method according to claim 1, characterized in that The concentration of the polyethylene glycol (PEG) aqueous solution in step (4) is 50 to 500 mg / ml.
8. A light / thermal responsive shape memory polyimide-based phase change composite material prepared by the method according to any one of claims 1 to 7.
9. Application of the light / heat responsive shape memory polyimide-based phase change composite material according to claim 8 in the preparation of heat storage materials, light-heat conversion and smart devices.
Citation Information
Patent Citations
Deformable aerogel material and preparation method thereof
CN110305360A
Cobalt cross-linked composite carbon aerogel with adjustable pore size, and preparation method thereof
CN110642250A